Relation Between Plea of Guilty and Defendants Right in RUU KUHAP (An Overview Through “Jalur Khusus” System) - Intan Khoirun Nisa'; Abdul Madjid; Setiawan Noerdajasakti (University of Udayana, 2023)
The stacks of cases in judicial institutions hinder achieving the principles of fast, simple, low-cost justice. Through the Drafting Team for the Criminal Procedure Code Draft, the intention is to try to adopt a system that commonly applies in the common law legal system, namely plea bargaining “jalur khusus”” which is shown in Article 199 of the RUU KUHAP. This research intends to examine the concept of plea of guilty used in special channels and to look for the relationship between giving a plea of guilty and the rights of the defendant. This research uses normative juridical research methods or library legal research using conceptual and analytical approaches. The technique for collecting legal materials used is the library research model. From this research it can be concluded that the plea of guilty given by the defendant to the indictment by the public prosecutor must be voluntary, in this case, the judge will assess the truth of the Plea of Guilty. It brings consequences that the trial process will faster for the defendant. However, ““jalur khusus”” do not specifically regulate what defendant right will release if he confesses to the charges, moreover there is a gap that need to be resolve. This has the potential for uncertainty for the defendant. Apart from that, there is no regulation regarding the right to file legal action which will have an impact on the defendant's right to obtain legal certainty regarding efficient time to achieve a speedy trial.